Pyrethroid Resistance Status of Aedes (Stegomyia) Aegypti (Linneaus) from Dengue Endemic Areas in Peninsular Malaysia - R, Rosilawati; HL, Lee; WA, Nazni; AH, Nurulhusna; A, Roziah; M, Khairul Asuad; F, Siti Futri Farahininajua; MY, Mohd Farihan; J, Ropiah (IIUM Medical Journal Malaysia, 2017)
Vector control is still the principal method to control dengue and chemical insecticides, especially the pyrethroids such as permethrin are the forerunners of mosquito control agent. Intensive and extensive use of pyrethroids often result in resistance, thereby hampering control efforts. The present study was conducted to evaluate the susceptible status of Aedes aegypti, the primary vector of dengue against permethrin. A nationwide mosquito sampling via ovitrapping was conducted in 12 dengue hotspots across 5 states in Peninsular Malaysia. Field collected Aedes eggs were hatched and reared until L3 larval and further identified it species. Adult F0 Aedes aegypti were reared until F1 progeny and the female were used in adult assay, performed according to World Health Organization (WHO) protocol as to determine the resistance level. The laboratory strain maintained for more than 1000 generations that were susceptible to permethrin served as the control strain. Evaluation of resistance ratio was assessed by comparing the knockdown rate with laboratory susceptible strain. In this present study, 70% ofAe. aegypti population from dengue hotspots was highly resistance to permethrin. The study clearly demonstrated that widespread of permethrin resistant Ae. aegypti in Malaysian mosquito’s population, indicating the need of implementing an efficient pyrethroid resistance management.